2018
DOI: 10.5535/arm.2018.42.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Cortical Stimulation (ECS) and Transcranial Direct Current Stimulation (tDCS) on Rats With a Traumatic Brain Injury

Abstract: Objective To evaluate the effects of electric cortical stimulation (ECS) and transcranial direct current stimulation (tDCS) on motor and cognitive function recovery and brain plasticity in focal traumatic brain injury (TBI) of rats model.MethodsForty rats were pre-trained to perform a single pellet reaching task (SPRT), rotarod test (RRT), and Y-maze test for 14 days, then a focal TBI was induced by a weight drop model on the motor cortex. All rats were randomly assigned to one of the three groups: anodal ECS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In the current study, we found that 4 weeks of CES treatment of TBI rats improved the recovery of locomotor function. These results parallel the findings from another TBI animal study, showing that CES is effective for the recovery of motor function, spatial memory (Yu et al, 2018 ). In addition, it has been found that the 100 Hz CES combined with daily motor training for 9 weeks significantly improved forelimb motor performance (Jefferson et al, 2016 ), encouraging further research into its therapeutic potential.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, we found that 4 weeks of CES treatment of TBI rats improved the recovery of locomotor function. These results parallel the findings from another TBI animal study, showing that CES is effective for the recovery of motor function, spatial memory (Yu et al, 2018 ). In addition, it has been found that the 100 Hz CES combined with daily motor training for 9 weeks significantly improved forelimb motor performance (Jefferson et al, 2016 ), encouraging further research into its therapeutic potential.…”
Section: Discussionsupporting
confidence: 88%
“…4b) associated to physical therapy [143]. This preliminary human result and some from animal studies [119, 227] have supported the potential benefit and safety of DCS after TBI. However, the diffuse damage associated with TBI, making it difficult to determine the stimulation target, could limit the use of tDCS as a therapeutic modality to improve motor outcomes after TBI.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 84%
“…Anodal stimulation hyperpolarizes apical dendritic layer (blue) and depolarize soma (red) of pyramidal cortical neurons. c The resultant tDCS effects reported are related to modified excitability [60, 63, 76, 118], neuroplasticity [8, 44, 45, 119] and neural network oscillation [67, 77, 120]. d Simulation of four brain networks during tDCS with a connectivity (or adjacency) matrix between a given pair of regions by connectivity strength [100, 102]…”
Section: Tdcs and Brain Connectivity On The Motor Cortexmentioning
confidence: 99%
“…This observed endogenous plasticity can be further investigated and manipulated using precise electrical modulation. To date, several methods have been explored to induce or accelerate functional and adaptive recovery in TBI patients, including both invasive (eg, electrical cortical stimulation [ECS]) and noninvasive (eg, transcranial magnetic stimulation [TMS], transcranial direct current stimulation, and pharmacologic) methods, each mediating an upregulation in plasticity following TBI [16][17][18][19][20]. However, animal studies and clinical trials involving the use of these interventions are scarce, and such approaches are often cell type indiscriminate, invasive, and render surrounding tissues susceptible to damage [21,22].…”
Section: Introductionmentioning
confidence: 99%